DETEKSI TINGKAT KEMATANGAN BERDASARKA WARNA BUAH JAMBU KRISTAL MENGGUNAKAN IMAGE PROCESSING - n/a Angellica; Raden Arief Setyawan; Muhammad Aziz Muslim (Jurnal Mahasiswa TEUB, 2023)
Crystal guava is a new guava variety that was developed in Taiwan in 1991, then developed in Indonesia in 2009 until now. Crystal guava is unique in terms of its texture and general shape. The advantages of crystal guava lie in its size, taste, and color. Fruit ripeness is usually determined by several parameters, including textural characteristics, fruit color and aroma, and others. Color is one of the parameters in crystal guava fruit ripeness. In determining the ripeness of crystal guava fruit based on color manually with the human visual eye, it has several disadvantages. Some of them are requiring more labor to sort the fruit, the assessment of ripeness by humans which is subjective and inconsistent in the point of view of vision between one assessor and another, and mental and physical workers such as fatigue, lack of focus and others can also affect the detection of the level of ripeness of crystal guava fruit. This tool was developed in order to help detect the level of ripeness of crystal guava fruit based on color moreconsistently according to the needs of crystal guava fruit farmers and the fatigue and lack of focus of workers can be avoided. Based on the test results show that the camera used is able to detect edges with a kernel size matrix value of 21x21. The camera can also detect the color hue of crystal guava fruit with the threshold value of canny edge detection is 40 and the threshold2 value is 150. Based on the test results it can also be concluded that the system has been tested with an accuracy value of detecting the level of ripeness based on the color hue of the crystal guava fruit of 96% and has an error of 4% of 100 samples of crystal guavafruit tested. Keywords : Crystal guava, Hue, Ripeness Level, Edge detect